2014
DOI: 10.1118/1.4890602
|View full text |Cite
|
Sign up to set email alerts
|

MCTP system model based on linear programming optimization of apertures obtained from sequencing patient image data maps

Abstract: A Monte Carlo treatment planning model exclusively based on maps performed from patient imaging data has been presented. The sequencing of these maps allows obtaining deliverable apertures which are weighted for modulation under a linear programming formulation. The model is able to solve complex radiotherapy treatments with high accuracy in an efficient computation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…This work showed that the MERT+IMRT plans were comparable or even better than those planned with conventional IMRT, and proved the possibility of planning APBI treatments by using MERT+IMRT without any additional equipment or specific device. Those plans were calculated using CARMEN, a full Monte Carlo treatment planning system developed by our group [18].…”
mentioning
confidence: 99%
“…This work showed that the MERT+IMRT plans were comparable or even better than those planned with conventional IMRT, and proved the possibility of planning APBI treatments by using MERT+IMRT without any additional equipment or specific device. Those plans were calculated using CARMEN, a full Monte Carlo treatment planning system developed by our group [18].…”
mentioning
confidence: 99%
“…This linac model has been previously validated for other published works [30] by comparison with experimental measurements of profiles and depth dose distributions corresponding to several field sizes (ranging from 2.4x2.4cm 2 to 16x21cm 2 ) obtained with ionization chamber and semiconductor diode. These results were achieved with a statistical uncertainty of less than 1%, and an agreement within 2% was obtained between experimental measurements and MC calculations.…”
Section: Methodsmentioning
confidence: 95%
“…At least, a compromise solution could be achieved by considering the dose prescription at the voxel level into an adequate optimization algorithm able to impose one or another prescription as appropriate to fulfill the global objective. In order to provide a solution to this problem, we implemented a linear programming (LP) formulation in our planning process [18]. LP based optimization allows to keep the molecular information from the functional image throughout the planning process, as demonstrated in a recent study [19].…”
Section: Methodsmentioning
confidence: 99%
“…To overcome the inadequate optimization method based on the traditional intensity maps when biological considerations have to be taken into account, we developed the BIOMAP algorithm [18], already implemented in CARMEN, which is based on a specific direct aperture optimization assumed to be more efficient for ART [29]. This algorithm takes into account both the morphological and the functional information by means of the generation of ray-tracing projections for each incident beam, which are managed as matrices under Boolean combinations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation